Development of empirical correlations for density and viscosity estimation of ternary biodiesel blends. (December 2021) - Mujtaba, M.A.; Kalam, M.A.; Masjuki, H.H.; Razzaq, Luqman; Khan, Haris Mehmood; Soudagar, Manzoore Elahi M.; Gul, M.; Ahmed, Waqar; Raju, V. Dhana; Kumar, Ravinder; Ong, Hwai Chyuan
Abstract: This study aims to investigate the density and viscosity of ternary biodiesel blends. Fuel density and viscosity play an important role in the fuel injection system, flame propagation, and combustion process in compression ignition engine. The density and viscosity of biodiesel are higher than high-speed diesel which is an implication in the commercialization of biodiesel. In the present study, palm oil has been used for the production of biodiesel through the ultrasound-assisted transesterification process. Three different types of fuel additives including butanol, dimethyl carbonate, and plastic oil have been used for the preparation of nine ternary biodiesel blends. The density and viscosity of individual fuels and ternary biodiesel were measured experimentally in a temperature range of 281.51 K–348.15 K. For the prediction of density and viscosity of ternary biodiesel blends, four density and viscosity models were developed. The prediction accuracy of these developed models was assessed by a statistical tool absolute percentage error (APE). Newly proposed exponential regression models predicted well compared to experimental data for density and viscosity values with high regression coefficient 0.9995 and 0.9841 and lower mean absolute percentage of error 0.012 % and – 0.516 % at (348.15 K) temperature respectively. These correlations are significant for the automobile industry in developing fuel pipeline and transport equipment where additives would be present in diesel-biodiesel fuel blends. Highlights: Exponential regression model show better prediction for density and viscosity. Density and viscosity of fuel blends were measured between 281.51 K and 348.15 K. Fuel additives effect on density and viscosity of ternary fuel blends. PO fuel additive exhibited closer density and viscosity values to diesel.